DEVELOPMENT OF CRITERIA FOR OPTIMUM MOORING CONFIGURATION OF TRUSS SPARS - INTACT AND DAMAGED LINE CONDITIONS - YENDURI, ANURAG (2014)
With increased exploitation of hydrocarbon reserves in deep offshore areas around the world, station-keeping of floating platforms becomes a more challenging task especially in terms of cost effectiveness. Installation of floating platforms in deep waters is encouraged by stronger environmental loads and hence, mooring system designed should be economical as well as performance efficient in intact and damaged line conditions. This research is undertaken to develop a criteria to optimise mooring configuration of truss spars that can aid especially during the preliminary design stage. The study includes developing MATLAB codes to compute the dynamic responses of truss spar platform and mooring system restoring forces respectively. In addition, a MATLABtool is developed using regrouping particle swarm optimisation technique to predict the optimum mooring configuration for a given truss spar platform.